Solid State NMR Characterization of Complex Metal Hydrides systems for Hydrogen Storage Applications - Son-Jong Hwang; Robert C. Bowman, Jr.; Chul Kim; Jason A. Zan; Joseph W. Reiter2 (Journal of Analytical Science and Technology, 2011)
Solid state NMR is widely applied in studies of solid state chemistries for hydrogen storage reactions. Use of 11B MAS NMR in studies of metal borohydrides (BH4) is mainly focused, revisiting the issue of dodecaborane formation and observation of 11B{1H} Nuclear Overhauser Effect.